Preliminares (2016)
Este documento contiene en texto completo el articulo Preliminares publicado en "Universidad & Empresa" Journal; Vol. 17, Núm. 29 (2015): (julio-diciembre,0); 1-8;Universidad & Empresa; Vol. 17, Núm. 29 (2015): (julio-diciembre,0); 1-8;2145-4558;0124-4639;10.12804/rev.univ.empresa.29.2015